PENGARUH UKURAN PERUSAHAAN, SOLVABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA PADA PERIODE 2018-2022 - Sasauw, Abigail; Tulung, Joy Elly; bin Hasan Jan, Arrazi (FEB Universitas Sam Ratulangi Manado, 2023)
This research aims to examine the influence of company size, solvency ration and liquidity ratio on company value. The population of this research is banking companies listed on the Indonesia Stock Exchange (IDX) with the research period 2018-2022. The sampling technique used was purposive sampling and a sample of 40 banks was obtained according to the specified criteria. The data analysis method used is Panel Data Regression Analysis with a Random Effect Model approach. The research results show that, partially, company size has a negative and significant effect on company value, solvency ratio (DER) has a positive and significant effect on company value and liquidity ration (LDR) has a negative and insignificant effect on company value. Simultaneously, company size, solvency ratio (DER) and liquidity ratio (LDR) influence company value in banking companies listed on the IDX for the 2018-2022 period.